2003
DOI: 10.1111/j.1745-4549.2003.tb00527.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microwave Power Level and Time on Ascorbic Acid Content, Peroxidase Activity and Color of Selected Vegetables

Abstract: 7ke objective of these studies was to evaluate the effects of blanching at various microwave power levels (30%. 55%, 70%, 100%) for various times (0, 1, 2, 3, 4 min) on peroxidase inactivation, and ascorbic acid and color preservation in broccoli, green beans and asparagus. As power level and time increased, moisture losses increased. Actual ascorbic acid concentration (mg/lOO g) increased, but when adjusted for moisture loss, it decreased.Microwave treatment at any power level for as little as 1 min reduced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
14
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 17 publications
6
14
0
3
Order By: Relevance
“…Ruiz-Ojeda and Peñas (2013) reported about 50% higher retention of vitamin C in microwaved blanched green bean pods in comparison with conventional hot water treatment. Similar results were reported by Muftugil (1986) and Brewer and Begum (2003) for microwaved green beans and by Ramesh et al (2002) for spinach, carrot and bell peppers. However, studies on the effect of MW blanching with subsequent conventional drying on the retention of bioactive compounds in fruits and vegetables including mango are lacking.…”
Section: Introductionsupporting
confidence: 89%
“…Ruiz-Ojeda and Peñas (2013) reported about 50% higher retention of vitamin C in microwaved blanched green bean pods in comparison with conventional hot water treatment. Similar results were reported by Muftugil (1986) and Brewer and Begum (2003) for microwaved green beans and by Ramesh et al (2002) for spinach, carrot and bell peppers. However, studies on the effect of MW blanching with subsequent conventional drying on the retention of bioactive compounds in fruits and vegetables including mango are lacking.…”
Section: Introductionsupporting
confidence: 89%
“…3). Similarly, Brewer et al (2003) observed that microwave treatment at any power level for as little as 1 min reduced peroxidase activity and retained ascorbic acid content in broccoli, green beans and asparagus.…”
Section: Bioactive Compounds Of Fresh Baobab Pulpmentioning
confidence: 76%
“…Microwave blanching allows for efficient heat transfer while requiring little or no water, which should reduce the amount of nutrients lost to leeching in comparison with boiling water immersion. Microwave blanching has been assessed over the years in a variety of fruits and vegetables, and, in general, has been found to be superior to conventional blanching methods (Kidmose and Martens 1999;Ramesh et al 2002;Brewer and Begum 2004).…”
Section: Introductionmentioning
confidence: 99%